Sistem Pertanian Pangan Adaptif Perubahan Iklim - Khudori Khudori (JURNAL PANGAN, 2011)
Tanpa upaya mitigasi dan adaptasi perubahan iklim, baik akibat kenaikan suhu, perubahan pola curah hujan, dan kenaikan muka air laut, sektor pertanian pangan akan mengalamikerugian yang amat besar. Ancaman penurunan produksi tanaman pangan strategis tidak hanya akibat perubahan iklim, tetapi juga karena kondisi infrastruktur waduk dan irigasi yang kurang memadai, serta berlanjutnya konversi lahan pertanian ke nonpertanian tanpa kendali. Belum lagi menghitung gagal panen akibat iklim ekstrim, serta serangan hama dan penyakit. Upaya mengurangi risiko gagal panen bisa dilakukan, baik yang bersifat struktural maupun non-struktural. Berbagai upaya yang bisa dilakukan, antara lain, pemetaan komoditas sesuai iklim, mengembangkan aneka jenis dan varietas tahan cekaman iklim, aplikasi informasi iklim, mengembangkan teknologi pengolahan tanah dan tanaman untuk meningkatkan daya adaptasi tanaman, dan mengembangkan sistem perlindungan usahatani dari kegagalan akibat perubahan iklim.Climate change significantly affects agriculture, especially the food crops. Without efforts to mitigate and adjust to climate change, not only to the increase in temperature and changes in rainfall patterns but also to the rise of sea levels, food agricultural sector will suffer huge losses. Threat of decrease in production of strategic food crops are not only due to climate change, but also inadequate condition of dams and irrigation infrastructure and the continued conversion of farmland to non-farm without control. It becomes worse if crop failure due to extreme climate and pests or diseases is also calculated. Efforts to reduce the risk of crop failure can be done, both in structural and non-structural ways. Various measures can be done, among others are: mapping of commodities according to climate, developing various types and climatic stress resistant varieties, applying climate information, developing soil and crop processing technology to improve crop adaptation, and developing a farm system protection from failures due to climate change.